Psychophysiological distinctions in emotional responding: sensitivity to perceiving loss of connection - Seah, Lily; Friedman, Bruce H. (Frontiers in Human Neuroscience, 2024)
Emotion involves oneself in relation to a subject of attention, e.g., sadness is to be sad about something/someone. This study examined emotional responses to perceiving a loss of connection from oneself. There is evidence that Europeans tend to perceive salient objects in the foreground, and East Asians tend to perceive holistically, including interrelationships between context and object. We studied how this distinction affected European Americans' (EA) and Chinese Americans' (CA) sensitivity to perceiving loss of connection. Both groups were exposed to loss playing Cyberball, a ball-tossing video game, and then watched a film clip on grief. We hypothesized that EA would respond with increasing heart rate (HR) variance around the mean when perceiving loss. CA were predicted to show no difference from controls. We also hypothesized that EA would feel sadder, in terms of decreased HR and increased Respiratory Sinus Arrythmia (RSA), earlier during the film clip. Fifty-three subjects were recruited, of which, 40 were EA (47.5% female, age 21.08±1.94) and 13 were CA (61.5% female, age 21.05±1.74). 25 subjects (19 EA, 6 CA) received 2 out of 48 balls tossed in Cyberball and the controls received 10. ECG, respiration, and facial electromyography (fEMG) data were acquired. Results during Cyberball showed that EA's HR variance relative to baseline (HR SDc/b) had an upward trend on perceiving loss. Contrary to prediction, CA also showed higher levels of HR variance relative to baseline. ANOVA of HR SDc/b revealed that the interaction effect of two factors, time and condition, were statistically significant (p=0.009). However, as predicted, EA in the experimental condition had decreased HR and increased RSA, a sign of withdrawal in sadness, 30 to 60 seconds into the sad clip. fEMG data at the corrugator muscle revealed that EA activated higher peak intensity 5.5 seconds earlier than CA (increased 1.571 vs 0.844). This difference, however, was not statistically significant. The evidence suggests that increased exposure to loss automatically led to increased HR variance in both groups even when subjects were informed that players were computer-generated. However, the effect was stronger on EA to increase their arousal and sensitivity to grief thereafter.